r1→ 0........1........1........−3
r2→ 1....−1........1........−7
r3→ 1........1........0............2
r1=r1+r2
1........0........2........−10
1....−1........1........−7
1........1........0............2
r2=r1−r2
1........0........2........−10
0........1........1........−3
1........1........0............2
r3=r3−r1
1........0........2........−10
0........1........1........−3
0........1....−2...........12
r3=r3−r2
1........0........2........−10
0........1........1........−3
0........0....−3...........15
r3=r3−3
1........0........2........−10
0........1........1........−3
0........0........1........−5
r2=r2−r3
1........0........2........−10
0........1........0............2
0........0........1........−5
r1=r1−2r3
1........0........00...........0
0........1........0............2
0........0........1........-5